The Corporate Tax Aggressiveness Dynamics In Indonesia : A Comparative Study Pre, During And Post COVID-19 - Rosvalya, Cut Bina; Tri Hanani (International Economic Conference of Business and Accounting, 2024)
The COVID-19 pandemic has caused major disruption to the global economy, affecting corporate revenues and financial stability. This research aims to (1) identify and evaluate changes in the level of corporate tax aggressiveness in three different time periods; before, during and after the COVID-19 pandemic, (2) identify patterns and trends in corporate tax behavior in each period. to understand whether there have been significant changes in tax aggressiveness related to economic conditions and government policies during the pandemic. This research uses a sample of 57 financial sector companies listed on the Indonesia Stock Exchange (IDX) during the 2016-2023 period. The data analysis method uses the Kruskal-Wallis test. The results show that tax aggressiveness before the COVID-19 pandemic was lower than during the pandemic, but higher than after the COVID-19 pandemic. In addition, this research contributes to providing new insights and empirical evidence to the academic literature on how global crises, such as the COVID-19 pandemic, impact corporate tax behavior.